Traditional foodstuffs and household food security in a time of crisis - Muhialdin, Belal J.; Filimonau, Viachaslau; Qasem, Jamal M.; Algboory, Hussein (Elsevier, 2021)
Traditional foodstuffs play an important role in household food security. No research has, however, attempted to examine traditional foodstuffs in light of disasters and crises. Such research can provide a useful outlook on how traditional foodstuffs can aid households in a situation of disrupted food supply. This outlook becomes relevant in view of future disastrous events that can undermine household food security, especially in poor disadvantaged communities. This study examined the role of traditional foodstuffs during a major crisis. The study adopted an ethnographic perspective and the method of semi-structured household interviews to explore how traditional foodstuffs were used by communities in the city of Mosul, Iraq, under the ISIS administration and during the liberation war (2016–2017). The study showcased the critical role of traditional foodstuffs in survival of local households. It highlighted the importance of cross-generational knowledge of traditional foodstuffs in community preparedness for disasters and crises. The study proposed to integrate traditional foodstuffs into governmental strategies on household food security in Iraq, and beyond. It suggested including traditional foodstuffs in the humanitarian food supply chains in the regions prone to disasters and crises. Future research should examine the prerequisites for such inclusion, especially from the viewpoint of societal and political acceptance of traditional foodstuffs and methods of their production.